Correction: Fluorescent glycoconjugates and their applications. (10th June 2021) - Thomas, Baptiste; Yan, Kai-Cheng; Hu, Xi-Le; Donnier-Maréchal, Marion; Chen, Guo-Rong; He, Xiao-Peng; Vidal, Sébastien
Abstract : Correction for 'Fluorescent glycoconjugates and their applications' by Baptiste Thomas et al., Chem. Soc. Rev., 2020, 49, 593–641, DOI: ; 10.1039/C8CS00118A .